EDU580 : Co-curriculum management / Faculty of Education - UiTM, Faculty of Education (Universiti Teknologi MARA (UiTM), 2023)
This course focuses on the philosophies, policies and practices of co-curriculum and co-curriculum management in schools. The course also covers the concepts, functions, guidelines and values of co-curriculum in schools. Particular emphasis is given on the management of co-curriculum activities which involves planning, implementation, supervision, evaluation, improvement and documentation of co-curriculum activities in schools. It will also look into the elements of participation in the three main co-curriculum activities which are sports and games, uniformed bodies, and clubs and societies. Current issues and trends relating to the management of co-curriculum activities in schools will also be discussed.